Evaluation of N and P mass balance in paddy rice culture along Kahokugata Lake, Japan, to assess potential lake pollution - Maruyama, Toshisuke; Hashimoto, Iwao; Murashima, Kazuo; Takimoto, Hiroshi (Paddy and water environment, 2008)
Kahokugata Lake, a closed lake, has been subject to eutrophication. This research was conducted to clarify the actual phenomena and evaluation of the discharges of N and P from paddy test fields in the lowlands into Kahokugata Lake. A comprehensive mass balance of N and P was obtained from 4 years of study. About N, the mean value of harvested unhulled rice (79.9 kg/ha) was greater than mean controlled release fertilizer inputs (56.7 kg/ha). Other inputs and outputs include N in atmospheric acid deposition (21.4 kg/ha) and N fixation–denitrification (9.2 kg/ha). The rice straw recycled after harvest was balanced by straw produced in the succeeding year. The runoff and percolation losses discharged into the lake was 11.3 kg/ha, (8.6% of total inputs). Since the rice harvested was consumed domestically, which taking out from the farmland and, therefore, nitrogen pollutant into the lake was becoming small, paddy rice at this site is considered an “anti-polluting, purifying or cleansing” crop. The P content in harvested rice (39.4 kg/ha) was balanced by fertilizer inputs (36.4 kg/ha). Previous studies examining inflow–outflow relationships without considering a comprehensive mass balance may lead to erroneous conclusions. Our findings indicate paddy rice in lowlands could be an environmentally friendly crop and can play an important role in reducing pollution of lakes, and therefore should be considered in land use planning.